Effectiveness of Injection of Trigger Points with Platelet Rich Plasma as A Pain Management Method in Rotator Cuff Syndrome - Algawwam, Hayder Ghali; Mohammad, Abdullah Ahmed (Journal of medical and pharmaceutical sciences, 2020)
Objective The aim of the current study is to evaluate the effectiveness of the injection of trigger points with platelet-rich plasma as a pain management method in chronic pain resulting from rotator cuff syndrome. Methodology A retrospective study was designed for the period from August 1, 2016, until July 31, 2019, 36 patients (21 females and 15 males) visited our private clinic in Kirkuk, Iraq because of chronic shoulder pain, they received trigger points PRP injections. The PRP was prepared by centrifuging the patient’s own blood. The response to therapy was graded: excellent, good, fair and poor. Results The mean age was 52.3± 1.9 years. Most of the patients (n: 33, 92%) had either overweight or obesity and (n: 16, 44.6%) had hypertension either alone or in combination with diabetes mellitus. Most of the patients (n: 30, 83.3%) received three sessions while (n: 6, 16.7%) received one session of PRP injections. Most of the patients (n: 28, 77.8%) yielded either good or excellent response to treatment, while (n: 8, 22.2%) from the patient had an either fair or poor response to treatment, there was a statistically significant difference (p˂0.01) between the 2 groups. Conclusion PRP injections of trigger points in patients complaining from chronic pain as a result of rotator cuff syndrome seem to be an effective, safe and cheap pain management method.